FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT TERHADAP OLAHRAGA TENIS MEJA DI INDONESIA - Manik, Swingly (Hanoman Journal: Physical Education and Sport, 2024)
Table tennis is a sport that is quite popular in Indonesia. This can be seen from the large number of people who play it, both professionally and recreationally. This sport is popular with various age groups, from children to adults. This research aims to identify the factors that influence people's interest in table tennis in Indonesia. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this research show that people's interest in this sport is caused by internal and external factors. Internal factors consist of liking for sports, individual abilities, playing experience, and perceptions of table tennis. Meanwhile, external factors consist of accessibility, promotion and socialization, athlete achievements and community support. In the modern era, with technological developments and increasingly dynamic lifestyles, there is great potential to increase Indonesian people's interest in the sport of table tennis.